Does an Implant Usage Report Card Impact Orthopaedic Trauma Implant Stewardship?. Issue 11 (November 2019) - Morellato, John; Baker, Mitchell; Isaac, Marckenley; Mixa, Patrick; O'Hara, Nathan N.; Okike, Kanu; Manson, Theodore T.; LeBrun, Christopher T.; Slobogean, Gerard P.; Nascone, Jason W.; O'Toole, Robert V.; Sciadini, Marcus F.; et al.
Abstract : Objectives: As hospitals seek to control variable expenses, orthopaedic surgeons have come under scrutiny because of relatively high implant costs. We aimed to determine whether feedback to surgeons regarding implant costs results in changes in implant selection. Methods: This study was undertaken at a statewide trauma referral center and included 6 fellowship-trained orthopaedic trauma surgeons. A previously implemented implant stewardship program at our institution using a "red-yellow-green" (RYG) implant selection tool classifies 7 commonly used trauma implant constructs based on cost and categorizes each implant as red (used for patient-specific requirements, most expensive), yellow (midrange), and green (preferred vendor, least expensive). The constructs included were femoral intramedullary nail, tibial intramedullary nail, long and short cephalomedullary nails, distal femoral plate, proximal tibial plate, and lower-limb external fixator. Baseline implant usage from the previous year was obtained and provided to each surgeon. Each surgeon received a monthly feedback report containing individual implant utilization and overall ranking. Results: The overall RYG score increased from 68.7 to 79.1 of 100 ( P < 0.001). Three of the 7 implants (tibial and femoral nails and lower-limb external fixation) had significant increases in their RYG scores; implant selections for the other 4 implants were not significantly altered. A decrease of 1.8% (95% confidence interval, 0.4–3.2, P = 0.01) was noted in overall implant costs over the study period. Conclusion: Our intervention resulted in changes in surgeons' implant selections and cost savings. However, surgeons were unwilling to change certain implants despite their being more expensive. Abstract : Supplemental Digital Content is Available in the Text.